The Malay principal form: A study of roof decorative elements of Rumah Limas Bumbung Perak / Iryani Abdul Halim Choo ... [et al.] - Abdul Halim Choo, Iryani; Abd Rashid, Mohd. Sabrizaa; Alauddin, Kartina; Jamaludin, Nazrul Helmy (Universiti Teknologi MARA, Perak, 2021)
This research aims to identify the Malay principal form in the roof decorative elements of Rumah Limas Bumbung Perak (RLBP). Through site observation, the data is collected in the form of images and analysed using the CAQDAS (Computer Assisted Qualitative Data Analysis Software) of Atlas Ti. 8. The findings of the research found that there are four Malay principal forms; Gunungan, Buah Guntung, Lebah Bergantung and Pohon Beringin present in the roof decorative elements of RLBP. The similarity and uniformity in the engagement of the form and its meaning is identifiable with the traditional houses of the other region which indicates a uniform understanding of the belief system and practises of the craftsmens throughout the Peninsula.